PENGARUH KEPEMILIKAN MANAJERIAL, FREE CASH FLOW DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN UTANG (STUDI PADA PERUSAHAAN-PERUSAHAAN INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BEI) - Hasan, Mudrika Alamsyah (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2014)
The purpose of this study is to obtain empirical evidence about the effect ofmanagerial ownership structure, free cash flow and the size of the companyscorporate debt policy and the Basic Industrial Chemicals listed in the StockExchange. The population in this study is a basic chemical sector companies listedin Indonesia Stock Exchange during the last three years, is from the years 2009-2011, by 43 companies, using purposive sampling and the sampling results obtained37 sample firms. The variables in this study there are two independent variablesconsisting of managerial ownership and free cash flow and firm size. The dependentvariable is the debt policy. It means that the higher the level of managerialownership of a company, the lower the ratio of debt to equity. Free Flow PositiveCash effects of debt policy (debt to equity ratio) at a significance level of 5%. Itmeans that the greater the value of the free cash flow value higher than the ratio ofdebt to equity and vice versa. The positive effect of firm size variable debt policy(debt to equity ratio) at 95% confidence level. This shows that the larger the size ofthe company it would be a higher value than the debt-to-equity ratio (DER).Managerial ownership, free cash flow, and the size of company policiessimultaneously significant effect of debt (debt-to-equity ratio) at 95% confidencelevel.Keywords: debt policy, managerial ownership and free cash flow, the size of the